The mediating effect of post‐stroke depression between social support and quality of life among stroke survivors: A meta‐analytic structural equation modeling. (1st November 2022) - Kuang, Jinke; Yang, Li; Lv, Runtian; Li, Jia; Zhou, Kexin; Xu, Mengfan
Abstract: Objectives: The aim was to confirm the relationship between social support (SS), post‐stroke depression (PSD), and quality of life (QOL) and determine the mediating effect of PSD in stroke survivors. Additionally, we tested the impact of economic development level (in developed or developing countries) on the relationship between SS, PSD, and QOL. Methods: This study utilized meta‐analytic structural equation modeling on systematically searched articles from PubMed, MEDLINE, Cochrane Library, Scopus, PsycINFO, Web of Science, China National Knowledge Infrastructure, and WanFang data published from inception to February 2022. Collect the sample size ( n ) of each study and the associations of observed variables, and conduct meta‐analysis path analysis using AMOS 23.0 to assess the relationships. Concurrently, the effects of the national economic development level were extracted for moderator analysis. Results: A total of 28 studies ( N  = 3967) were included for analysis. SS and PSD were significant predictors of QOL (both p  < 0.01). PSD mediated the relationship between SS and QOL ( β  = 0.31; 95% confidence interval 0.273–0.345; p  < 0.01). Furthermore, in developed countries, SS was not statistically correlated with PSD ( p  = 0.811) compared to developing countries. Conclusions: Improving SS may help improve the QOL of stroke patients. PSD should be addressed using a comprehensive approach that includes interventions to enhance the QOL. Additionally, people have different psychological reactions to SS at different stages of economic development; thus, further research is needed to develop different measurement standards for patients according to the country's level of economic development. Key points: The present study applied a novel approach, the Meta‐analytic structural equation modeling, to examine the relationship between social support (SS), post‐stroke depression (PSD), and quality of life (QOL) based on the main‐effect model and the stress‐buffering model. SS and PSD are significant predictors of QOL among stroke survivors. PSD mediated the relationship between SS and QOL. SS and PSD treatment are critical to positively influencing QOL for stroke survivors. Moderator analyses showed that people in countries with different levels of economic development have different psychological reactions to SS. Future research should explore the impact of national factors on SS, PSD, QOL, and related variables.